The Importance of Family Interview for Shaken Baby Syndrome - Emine Akkuzu; Gökhan Kalkan; Şule Demir; Figen Paslı; Aysu Duyan Çamurdan (Journal of Pediatric Emergency and Intensive Care Medicine, 2018)
Shaken baby syndrome (SBS) is caused by vigorous shaking of an infant by the arms, legs, chest, or shoulders. It must be thought when there is a suspicious story, subdural hemorrhage, bilateral retinal hemorrhage, cranial bone and or skeletal fracture, and ecchymosis. Here, we report a patient, who presented with seizures, with a family history of similar findings in his brother. Most of the efforts were given to find an organic reason to explain the patient’s findings due to the history of similar presentation of the sibling with an impression of inherited neuro-metabolic disorders and a negative result of a previous evaluation of the patient and the family for SBS at another hospital. Striking findings of SBS including subdural hematomas of different ages, occipital bone fracture, and retinal hemorrhages directed us to re-evaluate the family for SBS. After multiple episodes of family interviews, clues leading to injury through SBS were discovered. A single family interview may not be sufficient to exclude SBS especially in the presence of clinical findings. SBS is a diagnosis that should always be kept in mind in such patients, especially those with no organic cause.